2015
DOI: 10.1177/003335491513000616
|View full text |Cite
|
Sign up to set email alerts
|

Household Debt and Relation to Intimate Partner Violence and Husbands' Attitudes toward Gender Norms: A Study among Young Married Couples in Rural Maharashtra, India

Abstract: Findings suggest the need for combined gender equity and economic promotion interventions to address high levels of debt and related IPV reported among married couples in rural India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…Our findings indicated that money worries and food insufficiency created tension that resulted in conflict and IPV. The association between economic stressors and IPV have been demonstrated in previous work, and thus, are well-aligned with our findings [ 18 , 23 , 24 ]. One study conducted among couples in India found that debt was associated with increased IPV perpetration by male partners [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings indicated that money worries and food insufficiency created tension that resulted in conflict and IPV. The association between economic stressors and IPV have been demonstrated in previous work, and thus, are well-aligned with our findings [ 18 , 23 , 24 ]. One study conducted among couples in India found that debt was associated with increased IPV perpetration by male partners [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…One other major factor attributed to the increase in IPV during the COVID-19 pandemic has included economic stress due to disruption of income and earning power, resulting in reduced access to basic necessities and services [ 8 , 14 ]. Previous research has documented economic stressors experienced by males to be associated with increased IPV perpetration [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Money worries and food insu ciency created tension that resulted in con ict and IPV. The association between economic stressors and IPV have been demonstrated in previous work, and thus, are well-aligned with our ndings [18,21,22]. At times of economic austerity and emotional crisis, there may be an elevation in harmful alcohol consumption for IPV perpetrators; with those in remission relapsing and some potentially developing a new alcohol use disorder [13,23,24].…”
Section: Discussionsupporting
confidence: 89%
“…1315, 17 Both qualitative and quantitative research from India document that household financial stressors increase women’s risk for IPV, and impoverished women are more likely than middle and higher income women to work only to alleviate these financial stressors. 15, 17, 22 Financial inclusion services, such as bank account ownership or microloan use, may hold promise for reducing risk for IPV, as indicated by the above described intervention studies, but research has not examined associations of these services with IPV in India. Financial inclusion has increased dramatically in India since 2015, when the Prime Minister’s Pradhan Mantri Jan-Dhan Yojana initiative was launched to support bank account ownership in India.…”
Section: Introductionmentioning
confidence: 99%
“…We also explore whether observed associations are affected by husbands’ gender norms, specifically gender equity ideologies and attitudes regarding the acceptability of IPV, as these are related to IPV in India. 22, 25, 26…”
Section: Introductionmentioning
confidence: 99%